A model of nursing care for a patient after percutaneous closure of an atrial septal defect - Tkaczyk, Filip Miłosz (Nursing Problems / Problemy Pielęgniarstwa, 2022)
Cardiovascular diseases are among the most important challenges of modern medicine after oncological diseases. The aim of the study was to present a model of nursing care for a patient after percutaneous atrial septal defect (ASD) closure. Review method was analysis of literature on ASD and nursing care in invasive cardiology. The data were obtained from a review of the PubMed and Google Scholar electronic databases. Congenital anatomical anomalies of the ASD heart structure, in an advanced degree, lead to numerous accompanying diseases, such as frequent respiratory infections or severe circulatory failure. Summary care of the patient undergoing the ASD treatment procedure is carried out by a qualified interdisciplinary team. The provision of professional nursing care, taking into account the biopsychosocial needs of the patient, is a great professional challenge in the diagnostic and therapeutic process and postoperative recovery.